Growth and Production Response of Hydroponic Melon (Cucumis Melo L.) Using DFT System with Ab Mix and Gandasil B - Te'dang, Januar; Ario, Ario (CV. Publikasi Indonesia, 2025)
This study aims to evaluate the economic value of melon production using Gandasil B and its application effect on melon plants (Cucumis melo L.), as well as to determine the optimal dosage of Gandasil B that provides the most effective impact. The research was conducted in the Screen House of the Faculty of Agriculture, UKI Toraja, Tallunglipu District, North Toraja Regency. The method employed was a Randomized Block Design (RBD) with four treatment levels of Gandasil B foliar fertilizer: G0 (control, without Gandasil B), G1 (1 cc / liter of water), G2 (2 cc / liter of water), and G3 (3 cc / liter of water). The observed variables included plant height, number of leaves, number of branches, number of flowers, number of fallen flowers, fruit diameter, fruit weight, and total fruit weight per plot. Data were analyzed using Analysis of Variance (ANOVA) for RBD and followed by the Honestly Significant Difference (HSD) test. Gandasil B contains essential nutrients: nitrogen (6%), phosphorus (20%), potassium (30%), and magnesium (3%).